2019
DOI: 10.2147/ott.s193661
|View full text |Cite
|
Sign up to set email alerts
|

<p>The functions of microRNA-124 on bladder cancer</p>

Abstract: Background: To detect the expression of miR-124 in bladder cancer (BC) cell lines and tissue specimens and to analyze its association with the growth of the BC cells. Methods: Quantitative real-time polymerase chain reaction (qPCR) was applied to examine the expression of miR-124 in BC cell lines and tissues. The function of miR-124 in modulating cell proliferation was assessed in BC cells with miRNA-124 overexpression; the cell viability was identified by Cell Count Kit-8; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Emerging studies have implicated that miR-124 plays the tumor-suppressive role in the development of the human cancer and acts as a diagnostic prognostic biomarker for cancer [9][10][11][12][13]. For instance, downregulation of miR-124 was an independent prognostic factor in patients with colorectal cancer [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies have implicated that miR-124 plays the tumor-suppressive role in the development of the human cancer and acts as a diagnostic prognostic biomarker for cancer [9][10][11][12][13]. For instance, downregulation of miR-124 was an independent prognostic factor in patients with colorectal cancer [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes firmly suggest that miR-124 suppresses bladder tumor progression by targeting CDK4 in vitro and in vivo [12]. A study lead by Cao et al that was published in 2019 [13] used pairs of bladder cancer tissue and adjacent normal urothelium obtained from 83 bladder cancer patients together with bladder cancer cell lines (T24, 5637, J82, UM-UC-3), normal urothelium cells (SV-HUC-1) and human embryonic kidney cell lines (HEK293). MiR-124 expression was down-regulated in all bladder cancer cell lines compared with normal urothelium cell line, while the lowest levels of miR-124 were observed in T24 and 5637 cell lines.…”
Section: Reviewmentioning
confidence: 93%
“…It was noticed that over-expression of miR-124 led to down-regulation of CDK4, vascular endothelial growth factor (VEGF), E2F3 and Ki-67. However, all these changes were cancelled by CDK4 over-expression [13]. Aurora kinase A (AURKA) is an enzyme with an important role in cell division, during meiosis and mitosis.…”
Section: Reviewmentioning
confidence: 99%
“…Recent studies have revealed that the combination of AZ and SFN can also significantly reduce the sphere-forming ability and expression of CSCs markers such as Oct-4, Sox-2, and Nanog, thus suppressing cancer cell stemness ( Bayat Mokhtari et al, 2019 ). Additionally, miR-124, one of the most extensively studied microRNAs, has been demonstrated to inhibit BC cell proliferation through targeting CDK4 ( Cao et al, 2019 ). Interestingly, SFN suppresses the expression of stem cell markers (CD44 and EpCAM), IL-6R, STAT3, and p-STAT3 in a dose-dependent manner on the one hand, and on the other hand, significantly increases the expression of miR-124 in a dose-dependent manner.…”
Section: Effect Of Sulforaphane On Bladder Cancer Stem Cellsmentioning
confidence: 99%